Micronutrient Profiles in Severe Acute Malnutrition: Analyzing Vitamin B12, Zinc, Copper, Selenium, Manganese, Molybdenum, and Cobalt Levels: Micronutrient Profiles in Severe Acute Malnutrition - Bahalkani, Ubedullah; Ali Bharo, Mumtaz; Ali, Kamran; Bhanbhro, Bakhtiar Ahmed; Khuhro, Asif Ali; Ali, Faiza Kamran (Pakistan Journal of Health Sciences, 2024)
Severe Acute Malnutrition (SAM) is a critical public health issue affecting millions of people globally. Objective: To evaluate the status of micronutrients and their relationship with malnutrition severity. Methods: A cross-sectional study was conducted over six months from November 2023 to April 2024 at Pead’s Department Of Khairpur Medical College, KhairpurMirs. The study included 384 participants diagnosed with SAM. Micronutrient levels were assessed using quantitative colorimetry. Statistical analyses were descriptive, independent t-tests, Pearson and Spearman correlation analyses to evaluate micronutrient deficiencies. Results: The mean age of the children was 24.5 months, with a male predominance of 54.7%. Micronutrient levels showed significant variation between children with mild and severe malnutrition: p = 0.03), zinc (62.7 vs. 55.8 µg/dl, p = 0.01), vitamin B12 (312.4 vs. 278.6 pg/ml, p = 0.02), copper (97.3 vs. 89.2 µg/dl, p = 0.03), and selenium (45.7 vs. 40.2 µg/l, p < 0.05). Positive correlations between micronutrient levels and anthropometric variables were found by correlation analysis. Logistic regression indicated that deficiencies in Vitamin B12 (OR: 1.45, p = 0.02), Zinc (OR: 1.62, p = 0.01), and Copper (OR: 1.35, p = 0.03) were significant predictors of severe malnutrition. Conclusions: The findings emphasized that the need for targeted nutritional interventions addressing Vitamin B12, Zinc, and Copper deficiencies to improve health outcomes in malnourished children. Further research was essential to evaluate the impact of supplementation strategies on growth and recovery